Diet and experience of oral health during pregnancy with the incidence of stunting at Regional Public Hospital dr. Rasidin Padang: Pola makan dan pengalaman terhadap kesehatan rongga mulut semasa kehamilan dengan kejadian stunting di Rumah Sakit Umum Daerah dr. Rasidin Padang - Putri, Haifa Apiska; Khairunnisa, Haifa; Munawarah, Jihan Al; Zahwa, Lutifal Ramadhani; Attallah, Maisie; Surya, Leny Sang; Zia, Hanim Khalida; Pertiwi, Oniel Syukma; Pujianti, Alfiyah; Susanti, Desy (Makassar Dental Journal PDGI Makassar, 2025)
Stunting is a chronic nutritional problem in children under five years old, characterised by shorter height than their peers. Pregnant women are one of the groups that are vulnerable to oral and dental diseases, such as gingivitis, periodontitis, and caries. This stu-dy discusses diet and experience of oral health during pregnancy with the incidence of stunting at RSUD dr. Rasidin Padang; des-criptive research using quantitative data with a cross sectional research design using total sampling of questionnaires on 10 preg-nant women respondents. The results were the average age of respondents was 32 years and generally did not work. While in education the most respondents are elementary and high school education as many as 4 people. From the questionnaire it is known that respondents have a bad diet, while the experience of the respondent's oral health is moderate. It is concluded that maternal lifestyle also affects the nutritional status of toddlers so that it will also affect the growth and development of toddler teeth.